Kidney dysfunction is associated with mortality, adverse CT-based muscle metrics, and functional decline in surgically treated liposarcomas of the extremities and trunk - Julian Kylies; Fabian Haas; Anna Duprée; Tobias B. Huber; Karl-Heinz Frosch; Matthias Priemel; Dominik Kylies (PLoS ONE, 2026)
Background Liposarcomas (LS) of the extremities and trunk are aggressive soft-tissue sarcomas and surgical resection combined with multimodal therapy represents the cornerstone of curative treatment. Despite advances in surgical and medical management patients are still at risk of developing medical complications that negatively affect morbidity and mortality. Kidney dysfunction, sarcopenia and progressive loss of visceral adipose tissue have emerged as prognostically relevant and potentially treatable complications in surgical oncology. However, despite their growing relevance, little is known about their frequency and impact on survival and morbidity in the context of LS. Methods We conducted a retrospective study of 47 adult patients with localized LS of the extremities and trunk who underwent curative-intent surgery. Kidney function, CT morphometry of muscle (skeletal muscle index, SMI) and visceral adipose tissue (VAT) as well as clinical assessments including ECOG score were recorded at diagnosis (t1) and after a median follow-up (t2) of 11 months. Kidney dysfunction, defined as a decrease in eGFR of ≥ 25% between time points, was analyzed in relation to survival, sequentially assessed CT-morphometry of muscle and adipose tissue as well as functional status assessed by ECOG scores. Results All patients underwent curative-intent surgical treatment with or without additional multimodal treatment (surgery only: 51.1%, additional radiation: 31.9%, additional chemotherapy: 38.3%). Kidney dysfunction was frequent in our cohort (53.2% of all patients) and significantly associated reduced overall survival in Kaplan–Meier, uni- and multivariate Cox proportional hazards regression models (multivariate hazard ratio: 6.7; p = 0.03). In addition, patients with kidney dysfunction experienced a significantly accelerated loss of SMI (p < 0.001) and VAT (p < 0.001) as well as accelerated functional deterioration measured by worsening ECOG scores between t1 and t2 compared to a stable ECOG score in patients without kidney dysfunction (odds ratio of ECOG increase of: 8.0; p = 0.0027). Conclusions To our knowledge, this is among the first studies to investigate kidney dysfunction and its consequences in adult LS patients. In our cohort of surgically treated adult patients with LS of the extremities and trunk, kidney dysfunction was a frequent and clinically impactful complication. It was significantly associated with decreased overall survival, loss of muscle and adipose tissue in sequential CT morphometry assessments and progressive functional decline. Off note, CT-morphometry enabled objective, high-resolution tracking of body composition decline and may serve as a promising additional tool for risk stratification. Nonetheless, given the limited cohort size and retrospective single-center design, the generalizability of our findings is limited and the results should therefore be interpreted with caution. Despite these limitations, our findings call for future prospective studies and an awareness for heightened renal surveillance and integrated body composition assessments in the multimodal management of sarcoma patients.